Juridical Analysis of the Imposition of Imprisonment and Measures for a Juvenile Sexual Offender with Recidivist Status: A Study of Rokan Hilir District Court Decision Number 10/Pid.Sus-Anak/2025/PN Rhl - Sinaga, Dini Febrianti Br; Risdalina, Risdalina; Ritonga, Muhammad Khoirul (CV. Social Politic Genius (SIGn), 2025)
This research examines the law enforcement dilemma in sexual violence cases committed by a juvenile with recidivist status exhibiting characteristics of predatory behavior. This phenomenon palpably challenges the fundamental principle of child protection, which has traditionally prioritized out-of-court settlement (diversion). Unlike general approaches that tend to be trapped in a binary choice between retributive punishment or pure release, this research aims to analyze the rationality and effectiveness of applying the double track system in Decision Number 10/Pid.Sus-Anak/2025/PN Rhl. This decision serves as a legal response to the closure of diversionary programs for offenders who repeatedly commit crimes. By employing normative legal research methods through a case approach and supported by an in-depth analysis of recent literature, this research finds that the judge imposed combined sanctions consisting of 2 years and 6 months’ imprisonment and a 6-month job-training measure. The findings indicate that the judge’s consideration was based on proving systematic elements of violence, namely targeting, isolating, and overpowering. Furthermore, the juvenile recidivism status legally nullifies the right to diversion as regulated in Law Number 11 of 2012. This research concludes that in the context of a recidivist juvenile, legal protection is not manifested through release from charges. Conversely, protection is realized through structured mandatory rehabilitation within a closed institution. The theoretical and practical implications of this research recommend that law enforcement officials more explicitly include recidivism status and the offender’s risk profile as a basis for aggravating considerations in the verdict holding. This is crucial to ensure a balance between offender rehabilitation and societal protection from potential repeated crimes.